Identifying Key Parameters for Reducing Recombination Losses at the p-n Junction of Chalcopyrite Thin-Film Solar Cells - Amala Elizabeth; Harry Mönig (PRX Energy)
With a record efficiency of 23.64% achieved in the past year, Cu(In,Ga)Se_{2} chalcopyrites are the absorbers of choice for thin-film solar cells. In these devices, the p-type chalcopyrite absorber and the n-type window layer form the p-n junction at the interface, which is mediated by a thin buffer layer. Due to its close proximity to the p-n junction, the defect electronic properties of the absorber surface and its interface with the buffer layer are of significant importance to limit recombination losses of photogenerated carriers. Furthermore, the recent surge in the efficiency gains have been achieved with the aid of heavy alkali-metal elements, which are implemented via a postdeposition treatment of the absorber surface. Due to the complex defect physics of chalcopyrite materials, the effects and involved processes of these alkali-metal treatments are so far not well understood. As a fundamental requirement, understanding the intrinsic defect physics of chalcopyrite absorbers and how it is influenced by various surface treatments is of significant importance. In fact, it can provide a basis to develop knowledge-based strategies to reduce recombination losses due to the presence of electronic defect levels in the vicinity of the p-n junction. To experimentally access such defects at the surface, it is essential that the chosen characterization techniques possess high surface sensitivity. Furthermore, due to the pronounced crystallographic lateral inhomogeneities of the polycrystalline chalcopyrite thin films, a high spatial resolution is desirable. A combined analytical approach using scanning probe microscopy and spectroscopy or Kelvin force microscopy and photoelectron spectroscopy methods can provide valuable insights. Despite the extensive literature available on related topics, a consolidated view of the various findings made in this regard and the direct consequences for the device efficiency is still lacking. Our review addresses the significant progress made in understanding the defect electronic properties of the chalcopyrite surface in the past decade. The findings are consolidated into five sections, which illuminate several external sources of electronic defects and surface-passivation procedures. This allows to develop specific strategies to reduce interface recombination losses for device optimization and improved solar-cell efficiencies.